Partial rootzone drying: Regulation of stomatal aperture and carbon assimilation in field-grown grapevines (Vitis vinifera cv. Moscatel) - Souza, Cláudia R. de (2003)
The effects of 'partial rootzone drying' (PRD) irrigation compared with other irrigation systems, namely non-irrigated (NI), full irrigation (FI) and deficit irrigation (DI), on stomatal conductance and carbon assimilation were evaluated in field-grown grapevines (Vitis vinifera L. cv. Moscatel). At the end of the growing season, pre-dawn leaf water potential was highest in FI (–0.18 ± 0.01 MPa; mean ± s.e.), intermediate in PRD (–0.30 ± 0.01 MPa) and DI (–0.36 ± 0.02 MPa), and lowest in NI vines (–0.64 ± 0.03 MPa). Stomatal conductance measured under controlled conditions of light and temperature was reduced in NI (ca 60%) and PRD (ca 30%) vines compared with DI and FI vines. Under ambient conditions, NI vines had lower rates of stomatal conductance (ca 26%), net CO2 assimilation (ca 28%) and light-adapted PSII quantum yields (ca 47%) than PRD, DI and FI vines. No significant differences were found among the three irrigated treatments. Both maximum electron transport rate (Jmax; ca 30%) and triose-phosphate utilization rates (TPU; ca 20%) were significantly lower in NI and PRD vines than in DI and FI vines. Carbon isotope composition (δ13C) of grape berries was highest in NI vines (–24.3‰), followed by PRD (–25.4‰) and DI (–25.8‰) and lowest in FI (–26.4‰) vines, suggesting a long-term increase in the efficiency of leaf gas exchange in NI compared with PRD, DI and FI vines. Sap-flow data and estimates of relative stomatal limitation are in accordance with the observed stomatal closure in PRD vines. In this study, we show that PRD irrigation was able to maintain a vine water status closed to FI, but with double water use efficiency, which was due to a reduction of stomatal conductance with no significant decrease in carbon assimilation.